Sebaceous Differentiation in Squamous Cell Carcinoma of the Larynx and Adjacent Pharynx: Case Report with Review and Discussion of the Literature - Cardesa, Antonio (Head Neck Pathol, 2017)
Among the variants of squamous cell carcinoma (SCC) of the head and neck arising in mucosal surfaces, examples with sebaceous differentiation are exceedingly rare. We present a new case of SCC with sebaceous differentiation, developing in the larynx of a 64 year-old male, cigarette smoker and alcohol drinker. The tumor extended transglottically, metastasized to cervical lymph nodes, and killed the patient after 12 months. Comparing this case with four previously reported cases of SCC with sebaceous differentiation, two arising in the larynx and the other two in the adjacent pharynx, all five patients mostly shared the following features: appearance of the tumor in the seventh decade of life, heavy tobacco smoking, alcohol intake in three, surgery as mainstay treatment, tumor size between 2 and 4.7 cm, and regional lymph node metastases in four of them. Out of the four patients with a follow up of 12 months, two died of disease, one was alive with disease, and only one was alive without disease. One patient was lost for follow up. In conclusion, mucosal SCC with sebaceous differentiation is a very rare variant of SCC that when arising in the larynx and anatomically adjacent parts of the pharynx behaves aggressively and bears a dismal prognosis. The recognition of new cases of this entity requires special awareness of its phenotypic features and may be important for further assessment of its behavior.